Factors affecting metastases to non-sentinel lymph nodes in breast cancer. Issue 1 (23rd December 2003) - Fleming, F J; Kavanagh, D; Crotty, T B; Quinn, C M; McDermott, E W; O'Higgins, N; Hill, A D K
Abstract : Aims: Because sentinel lymph node (SLN) biopsy for breast cancer has become well established, one of the challenges now is to determine which patients require a completion axillary dissection following a positive SLN biopsy. Methods: A prospective database of patients who underwent SLN biopsy for invasive breast cancer from July 1999 to November 2002 (n = 180) was analysed. Fifty four patients (30%) had one or more positive SLN, and all underwent a completion axillary dissection. This subgroup was further analysed to delineate which factors predicted non-SLN metastasis. Results: Twenty six of the 54 patients with a positive SLN had additional metastases in non-SLNs. Significant variables that predicted non-SLN metastasis included extranodal extension (odds ratio (OR), 17.399; 95% confidence interval (CI), 1.69 to 178.96) and macrometastasis within the SLN (OR, 6.985; 95% CI, 1.291 to 37.785). Conclusions: In patients with invasive breast cancer and a positive SLN, extranodal extension or macrometastasis within the SLN were both independent predictors of non-SLN involvement.